The Gulag in East Germany : Soviet special camps, 1945-1950 - Merten, Ulrich 1930- (Teneo Press, 2018)
Overview of the special camps -- Western Allied internment camps and the denazification of Germany -- Denazification in the Soviet zone of occupation -- Security organization in the Soviet zone of occupation -- Establishment of the special camps -- The prisoners : who were they? -- Life and death in the Spezlager -- Prisoner release and the closing of the camps -- The Waldheim trials and last thoughts -- Addendum: Forced labor in the Soviet uranium mines of Eastern Germany.